KEDUDUKAN DAN FUNGSI KOMISI PERLINDUNGAN ANAK INDONESIA DALAM MELINDUNGI HAK-HAK ANAK - Apri Rotin Djusfi (Jurnal Public Policy, 2016)
Indonesian Child Protection Commission is an independent agency, established under the provisions of the Law on Child Protection. Was formed on June 21, 2004, this agency is mandated by Presidential Decree No. 77 of 2003 and Article 74 paragraph (1) and (2) of Law 35 of 2014 on the Amendment of Act No. 23 of 2002 on Child Protection. The problem that is revealed in this research is how the protection of children is in conformity with the principles of human rights, is child protection in Indonesia is in conformity with the 1945 Constitution and the laws protecting children and how the role of the Indonesian Child Protection Commission in protecting the rights of children. The principles of human rights that protects the protection of children one of which is the birth certificate. Indonesian Child Protection Commission’s role in protecting the rights of children is as a protection and supervisor of Law 35 of 2014 on the Amendment of Act No. 23 of 2002 in the Child Protection.Keywords : Children Right Protection Law,  KPAI, Children's rights